Profile of Glomerular Filtration Rate Estimation Using the CKD-EPI Method in Type 2 Diabetes Mellitus Patients: Assessing the Risk of Kidney Complications - Metana Puspitasari; Eko Dewi Ratna Utami (Sarana Ilmu Indonesia (Salnesia), 2026)
Diabetes mellitus is a metabolic disease that occurs due to the body's inability to produce and/or use insulin effectively, resulting in high blood sugar levels. Type 2 diabetes mellitus (DM) accounts for 90% of all diabetes cases globally, with significant contributing factors such as obesity, sedentary lifestyles, and poor dietary habits. In 2019, Indonesia ranked seventh in the world for the number of diabetes cases, with 10.7 million individuals affected. This research used a retrospective, observational, descriptive-analytic approach to assess kidney dysfunction in newly diagnosed type 2 diabetes mellitus patients, using the CKD-EPI equation to estimate eGFR.. The eGFR analysis revealed that most patients had eGFR values below the normal threshold of <90 mL/min/1.73 m², with an average of 77.5 ± 28.51 mL/min/1.73 m², indicating kidney impairment at the early stage. The largest group (45%) showed normal kidney function, while 21% had mild dysfunction. Patients with kidney impairment (eGFR < 90 mL/ min/ 1.73m²) had a higher average fasting blood glucose level (240 ± 82.9 mg/dL) compared to those without kidney impairment. These findings emphasized the importance of early detection and intervention for managing both blood glucose levels and kidney function effectively. Early detection of kidney impairment in type 2 diabetes mellitus patients is crucial in preventing further complications and preserving kidney health.